ANALISIS STRATEGI TUTUR PERSUASIF PADA PODCAST BERJUDUL LIFE HACK BELAJAR DAN UJIAN ALA MAUDY AYUNDA DALAM CHANNEL YOUTUBE KOKBISA? - lubis, sarah (FKIP, Universitas Palangka Raya, 2023)
Speech acts are utterances made as part of social interaction. A speech act is an utterance of a sentence to state so that a speaker’s intention can be known by the listener. This study aims to analyze persuasive speech strategies in the podcast entitled Maudy Ayunda’s life hack learning and exam on the Howto? As well as finding persuasive (inviting) speech acts in the podcast. This study uses qualitative research with descriptive methods. This technique is used to observe the speech delivered by Maudy Ayunda which will be analyzed by researchers. The results of this study indicate that there are persuasive (inviting) speech acts so that the audience can take part in the lifehack conducted by Maudy Ayunda in studying and exams.Maudy Ayunda’s delivery strategy was persuasive (invitation) when she tried to convince through expressions and facial expressions that seemed to convince listeners and spectators to be able to follow the way she studied and faced exams.